4-Benzyloxy-1,1'-biphenyl - Adam, Farook; Ameram, Nadiah; Dhiraj Kamath, Shevgoor; Pallavi, Pallavi; Samshuddin, Seranthimata (International Union of Crystallography, 2016)
In the title compound, C19H16O, the dihedral angle between the benzene rings of the biphenyl unit is 1.54 (13)° and the C—O—C—C torsion angle is 174.4 (2)°. In the crystal, very weak C—H...n interactions link the molecules into a threedimensional network. Many diaryl ethers exhibit various pharmacological properties including anti-bacterial, anti-inflammatory, antifungal and herbicidal activities (Ley & Thomas, 2003; Frlan & Kikelj, 2006). The crystal structures of some aryl ethers viz., 2,4-dichloro-1-[1-(2,4 dichlorobenzyloxy) ethyl]benzene (Jasinski et al., 2010) and 2,6-bis[2-(4-benzyloxyphenyl) ethyl]biphenyl (Moratti et al., 2007) have been reported. As part of our studies in this area, the synthesis and structure of the title compound are reported.